Estriol (local and systemic forms) in the treatment of atrophic vulvovaginitis - V N Prilepskaya; A V Ledina (IP Berlin A.V., 2015)
Atrophic processes of the urogenital tract, and atrophic vulvovaginitis are an actual gynecological problem due to declining estrogen levels. Diagnosis of this condition is not difficult, based on characteristic clinical picture of the disease, but requires an examination of cytological control. Treatment is based on the shortfall of estrogen. This predominance of symptoms of urogenital atrophy requires estriol based treatment in its local forms.